Unravelling the success factors of Latin-American Fair Trade projects - Valdivieso-Albán, Sebastián (2024)
This investigation seeks to identify the success factors of Latin-American Fair Trade projects through a systematic literature review with the Kitchenham and Charters method. Through a data extraction and its evaluation from selected literature, to the online libraries Scopus, Web of Science, Redalyc, Springer Link and Science Direct in the range from 2018 to 2023 it determines that the success factors are government support, production increase, capacity building and skills promotion, and international market outreach. It also identifies that these factors depend on complementary factors related with the capacity of producers and workers to implement these Fair Trade certifications and practices in their production, mainly in agriculture. These factors benefit community-based projects from vulnerable groups in rural areas while correlating to exports and Fair-Trade principles. Meaning, certification is not compulsory, so its principles can be implemented in a variety projects, generating a series of benefits and limitations for their development.